2022
DOI: 10.52312/jdrs.2022.645
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the femoral entry point for intramedullary alignment in total knee arthroplasty: A computer-aided design approach

Abstract: Objectives The aim of this study was to simulate different entry points and investigate potential angulation errors of the intramedullary device and resulting changes in the distal femoral cut using a computer-aided design (CAD) approach. Materials and methods We used a CAD approach to simulate various distal femoral entry points for intramedullary instrumentation. Simulations were performed on (i) a commercially available three-dimensional (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Total knee arthroplasty is one of the widely performed orthopedic surgeries worldwide; achieving a pain-free and functional joint, along with high patient satisfaction, are among the goals of this surgery. [ 1 ] Patient, surgeon, and implantrelated factors influence the outcomes. One of the patient-related factors is the morphological changes of the distal femur and proximal tibia, which contribute to the formation of the knee joint surface.…”
Section: Introductionmentioning
confidence: 99%
“…Total knee arthroplasty is one of the widely performed orthopedic surgeries worldwide; achieving a pain-free and functional joint, along with high patient satisfaction, are among the goals of this surgery. [ 1 ] Patient, surgeon, and implantrelated factors influence the outcomes. One of the patient-related factors is the morphological changes of the distal femur and proximal tibia, which contribute to the formation of the knee joint surface.…”
Section: Introductionmentioning
confidence: 99%
“…1 Some studies may vary 9.2mm anterior to and 3.6mm medial to Anterior Intercondylar notch. 4 Literature review shows no clear research work comparing long and short alignment rod for femur and its impact on alpha angle.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that improper prosthesis placement and positioning would affect clinical outcomes by causing aseptic prosthesis failure, instability, and premature wear of polyethylene. [ 3 ] Studies have shown that proper alignment of these components is essential for better postoperative outcomes and the long-term survival of TKAs. [ 4 ] Numerous instruments have been developed for the correct implantation and execution of surgery.…”
Section: Introductionmentioning
confidence: 99%